Two new species of Eucyclops Claus (Copepoda: Cyclopoida) from the Chihuahuan Desert with a redescription of E. pseudoensifer Dussart - Suárez-Morales, Eduardo; Walsh, Elizabeth J. (Zootaxa, 2009)
Two new species of the freshwater copepod genus Eucyclops are described from two sites in the Chihuahuan Desert (CHD), which includes parts of northern Mexico and southern United States. Eucyclops cuatrocienegas sp. nov. is distinguished by having a short inner spiniform seta on the fifth leg, relatively short caudal rami, and a partially naked spine of the fourth endopod, among other characters. The finding of E. cuatrocienegas in Cuatro Ciénegas, an area in the CHD that is known for harbouring the highest number of endemic aquatic species in North America, suggests that these habitats could yield other endemic forms. The other new species resembles the Neotropical E. pseudoensifer Dussart, 1984 but differs in having a shorter basipodal spine of the first leg, shorter outer terminal spiniform caudal seta, a different length ratio of inner/outer spines of leg 4 third endopodal segment, and a different pattern of the serra on the caudal rami. Eucyclops pseudoensifer, originally collected from a high altitude lake in the Andean system of western Venezuela, is here redescribed from female and male type specimens. The description of E. chihuahuensis sp. nov. recognizes both the subtle but consistent differences of this population and its environmental isolation in this arid region. The North American records of E. pseudoensifer should be revised in the light of these findings in order to determine the real distributional ranges of these species.